2014
DOI: 10.4193/rhin13.066
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical disfunction in the mucosal oedema formation of patients with nasal polyps

Abstract: The interstitial hydrostatic pressure showed different behaviour during liquid infusion in nasal mucosa from NP patients when compared with healthy nasal mucosa. This study allows us to cogitate on a new pathophysiological mechanism contributing to the development of the NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…18 Despite the fact that the polypoid nasal mucosa is empirically recognized as a soft tissue, and that the nasal mucosa in chronic sinusitis without nasal polyposis is empirically recognized as a fibrotic tissue, only in 2014 it was confirmed for the first time that the nasal mucosa of patients with NP is more conducive to edema formation through biomechanical dysfunction. 19 This same study demonstrated that not only the polypoid tissue, but the entire nasal mucosa of patients with NP exhibits a form of mechanical dysfunction, and that this dysfunction varies according to the region of the nasal mucosa. Subsequent biomechanical studies have shown that a healthy nasal mucosa also exhibits different mechanical properties depending on the region, which provides further evidence against the use of the lower-turbinate mucosa as a control tissue in studies of middle meatus diseases, such as NP.…”
Section: Introductionmentioning
confidence: 82%
“…18 Despite the fact that the polypoid nasal mucosa is empirically recognized as a soft tissue, and that the nasal mucosa in chronic sinusitis without nasal polyposis is empirically recognized as a fibrotic tissue, only in 2014 it was confirmed for the first time that the nasal mucosa of patients with NP is more conducive to edema formation through biomechanical dysfunction. 19 This same study demonstrated that not only the polypoid tissue, but the entire nasal mucosa of patients with NP exhibits a form of mechanical dysfunction, and that this dysfunction varies according to the region of the nasal mucosa. Subsequent biomechanical studies have shown that a healthy nasal mucosa also exhibits different mechanical properties depending on the region, which provides further evidence against the use of the lower-turbinate mucosa as a control tissue in studies of middle meatus diseases, such as NP.…”
Section: Introductionmentioning
confidence: 82%
“…Our finding of higher pressure in the middle turbinate from healthy nasal mucosa than in nasal polypoid tissue corroborates a previous study. 6 The higher IHP found in fibrotic tissue (synechiae) after saline infusion when compared with polypoid nasal mucosa Fig. 2 (A) Comparison of pressure increase in nasal polypoid tissue versus healthy nasal mucosa (middle turbinate), the pressure increase is greater in healthy middle turbinate than in polypoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A 22-gauge needle coupled to a Controlled Disc Stimulation device (CDS, Smith & Nephew, Memphis, TN, USA) was used to inject the controlled volume within the submucosa to measure local pressure. 6 All patients were under general anesthesia, and received no intranasal drugs before the saline injection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations